(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The teaching of English has undergone tremendous changes over the years, which currently require using alternative approaches, such as the development of communication, life skills, interpersonal skills, and ICT literacy in foreign language teaching. This article will discuss applying the most appropriate methods, techniques, modern ICT devices according to students’ learning styles in teaching English